IMPLEMENTATION OF THE PROMOTHE METHOD IN THE DECISION SUPPORT SYSTEM TO DETERMINE THE LEARNING GUIDE: IMPLEMENTATION OF THE PROMOTHE METHOD IN THE DECISION SUPPORT SYSTEM TO DETERMINE THE LEARNING GUIDE - Agustina Simangunsong (Institute of Computer Science (IOCS), 2020)
In learning to teach not only the students who evaluated the results of the study, the Tentor also evaluated the teaching and learning system, this is done to know the feasibility and quality of the tentor who teaches so that it is known which has a good and professional performance description. In determining the best sort order often appears subjectivity of decision makers, therefore there are often mistakes so that there is a problem that causes the effort to determine the order of the achievements of the tentor that will be rewarded, from this can cause jealousy for each tentor who feel himself best but do not get the award as it should. The Promethee method is a method used in multicriterion order determination or prioritization. The Promothee method is a very efficient and simple method, and is easy to implement compared to other methods of completing multicriterion-based problems. Testing the application of decision support system to determine the best tentor, in the decision to use the sample data results achieved in the following three ways: Leaving Flow, Entering Flow and Net Flow.